2010
DOI: 10.1038/ng.642
|View full text |Cite
|
Sign up to set email alerts
|

Common genetic variation in the HLA region is associated with late-onset sporadic Parkinson's disease

Abstract: Parkinson disease (PD) is a common disorder that leads to motor and cognitive disability. We performed a genome-wide association study (GWAS) with 2000 PD and 1986 control Caucasian subjects from NeuroGenetics Research Consortium.1–5 We confirmed SNCA2,6–8 and MAPT3,7–9; replicated GAK9 (PPankratz+NGRC=3.2×10−9); and detected a novel association with HLA (PNGRC=2.9×10−8) which replicated in two datasets (PMeta-analysis=1.9×10−10). We designate the new PD genes PARK17 (GAK) and PARK18 (HLA). PD-HLA association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
639
3
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 714 publications
(670 citation statements)
references
References 35 publications
22
639
3
6
Order By: Relevance
“…For AD, Yokoyama et al22 showed that eight variants were associated with both AD and immune‐mediated diseases, and there is further evidence from pathway analysis1, 23, 24 and from animal models 25. For PD, the role of the immune system has been suggested through pathway analyses,26, 27 animal models,28 and variants in the Human Leukocyte Antigen (HLA) region reaching statistical significance in GWASs 3, 29. For ALS, there is evidence of immune abnormalities 30.…”
Section: Introductionmentioning
confidence: 99%
“…For AD, Yokoyama et al22 showed that eight variants were associated with both AD and immune‐mediated diseases, and there is further evidence from pathway analysis1, 23, 24 and from animal models 25. For PD, the role of the immune system has been suggested through pathway analyses,26, 27 animal models,28 and variants in the Human Leukocyte Antigen (HLA) region reaching statistical significance in GWASs 3, 29. For ALS, there is evidence of immune abnormalities 30.…”
Section: Introductionmentioning
confidence: 99%
“…In the GWAS carried out by Hamza et al, 10 only one SNP (rs3129882) in this region exceeded genome-wide significance level. After in silico replication and meta-analysis of the most significant SNPs, another six SNPs in this region were associated with PD in their population.…”
Section: Hla Regionmentioning
confidence: 99%
“…In a first approach aiming to determine (in the Dutch) the role of previously identified PD genetic risk factors, we decided to look closely at the results for SNCA (chromosome 4q21), [5][6][7] MAPT locus (chromosome 17q21.1), 5,7 LRRK2 (chromosome 12q12), 6,7 PARK16 6,7 (chromosome 1q32), BST1 (chromosome 4p15), 6 the GAK/DGKQ locus (chromosome 4p16), 5 the HLA region (chromosome 6p21.3) 10 and chromosome 12q24 locus. 11 A total of 30 SNPs from these loci were selected for closer scrutiny.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, our understanding of idiopathic PD has been enhanced by genome‐wide association (GWA) studies6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16 that have collectively identified PD risk variants at >18 loci 6, 7. Despite their high levels of significance, these 18 loci are thought to account for only a very small amount (3–5%) of the expected heritability of PD 17.…”
mentioning
confidence: 99%